Studies on the stereoselective synthesis of sacubitril via a chiral amine transfer approach - Sadanande, Megha V.; Thorat, Sagar S.; Sharma, Himanshu; Singh, Geetika; Vanka, Kumar; Gonnade, Rajesh G.; Kontham, Ravindar (Chemistry-An Asian Journal, 2025)
We present a comprehensive account of our efforts directed towards the synthesis of sacubitril, a neprilysin inhibitor used in combination with valsartan and marketed as Entresto (TM). Our initial approach to the formal synthesis of sacubitril employed a chiral pool strategy, utilizing (S)-pyroglutamic acid as a key building block and Cu(I)-mediated Csp2-Csp3 cross-coupling as a key transformation. Further investigations led to the development of chiral amine transfer (CAT) reagents-based stereoselective synthesis. This involved the E-selective construction of gamma-ylidene-butenolide from readily available biphenyl bromide and 4-pentynoic acid, the conversion of this butenolide to its ene-lactam using chiral amine, and substrate-controlled diastereoselective reduction of ene-lactam using Et3SiH or Pd/C, H2 (overall chiral amine transfer) as key transformations. Antipodal lactam intermediates were synthesized using corresponding chiral amines, and the stereochemical outcomes during the ene-lactam reduction with Et3SiH were rationalized by DFT studies.
Keywords: Chiral Amine Transfer (CAT) approach; Chiral pool approach; Sacubitril; stereoselective synthesis